Androgens and obesity in male adolescents. Issue 3 (June 2015) - Vandewalle, Sara; De Schepper, Jean; Kaufman, Jean-Marc
Abstract : Purpose of review: Data on sex steroid levels and pubertal development in obese adolescent boys are scarce and contrasting. The present review summarizes the most recent results obtained with improved methodology to measure low sex steroid levels in children. Recent findings: Obese pubertal boys have lower serum sex hormone–binding globulin and consequently lower total testosterone levels compared to normal-weight peers. However, during pubertal development, free testosterone levels in obese adolescents are not different from controls, indicating preserved androgen exposure as is additionally suggested by similar clinical genital staging (Tanner), serum gonadotropins levels, and serum prostate-specific antigen concentrations compared to nonobese adolescents. In pre and early puberty, total testosterone levels is not decreased, notwithstanding low sex hormone-binding globulin, and free testosterone is slightly increased in obese boys. This may result from increased adrenal activity as revealed by elevated serum androstenedione and dehydroepiandrosterone sulfate. In obese adolescent boys, increased aromatization of testosterone to estradiol tends to accelerate skeletal maturation. Summary: In obese adolescent boys, free testosterone is a better index than total testosterone levels of androgen status, which is not different from nonobese controls. Increased aromatization of testosterone to estradiol underlies the dissociation between normal clinical sexual maturation and advanced skeletal maturation in the obese adolescent.